Analisis Analisis Peran Interactive Flat Panel (IFP) dalam Mendukung Hasil Belajar Matematika Siswa Kelas VI SDN Labuhan Lalar - Khairul Ikhsan (Journal of Elementary Education Research, 2026)
Mathematics is one of the essential subjects in elementary school because it plays an important role in developing students’ logical, critical, and systematic thinking skills. However, various obstacles are still found in mathematics learning, especially in the topic of standard units. Many sixth-grade elementary school students experience difficulties in understanding the concepts of length, weight, time, and volume because the learning process is often still conventional and less supported by attractive learning media. As a result, student learning outcomes in standard unit material have not reached optimal achievement. The rapid development of educational technology has introduced various digital learning media that can assist teachers in creating more interactive and engaging learning environments, one of which is the Interactive Flat Panel (IFP). IFP is an interactive touchscreen device that can display learning materials, videos, animations, and practice exercises directly, enabling students to participate actively during the learning process. The use of IFP in mathematics learning can help students understand standard unit concepts through clearer visualization and direct practice activities. This study aims to analyze the role of Interactive Flat Panel (IFP) in supporting mathematics learning outcomes of sixth-grade students at SDN Labuhan Lalar. This research employed a descriptive qualitative method with a literature review approach. Data were collected through the exploration and analysis of academic documents, including scientific journals, books, and conference proceedings obtained from Google Scholar. The data were analyzed using thematic content analysis to identify important concepts, patterns, and findings. The findings indicate that the implementation of IFP in mathematics learning contributes positively to increasing students’ attention, motivation, conceptual understanding, and learning outcomes. Therefore, the use of IFP can be considered an effective learning medium in supporting elementary mathematics education.